Development of light-shielding hydrogel for nitrifying bacteria to prevent photoinhibition under strong light irradiation. (July 2020) - Nishi, Kento; Akizuki, Shinichi; Toda, Tatsuki; Matsuyama, Tatsushi; Ida, Junichi
Graphical abstract: Highlights: Light-shielding hydrogel successfully mitigated photoinhibition of their nitrifying performance from strong light irradiation. In the hydrogel, nitrifying bacteria and carbon black powder were encapsulated. Use of the Light-shielding hydrogel can effectively mitigate the photoinhibition. Abstract: Microalgae-nitrifying bacteria consortia have gained attention because photooxygenation of algae can supply oxygen to bacteria which eliminates the need for costly mechanical aeration. However, nitrifying bacteria are known to suffer from photoinhibition. In this study, we developed "Light-shielding hydrogel", in which bacteria were immobilized in hydrogel and light-shielding particles (carbon black) were incorporated, and evaluated its effectiveness to mitigate photoinhibition for bacteria under strong light irradiation. For comparison, "Hydrogel", in which bacteria were immobilized in hydrogel without carbon black, and "Dispersion" which was simply suspended bacteria were prepared. At 1600 μmol photons m −2 s –1, the nitrification performance markedly decreased to 15.1 and 48.0% compared to the dark condition in the Dispersion and the Hydrogel, respectively. Meanwhile, it was successfully maintained for the Light-shielding hydrogel. Our results showed that the effectiveness of light-shielding hydrogel to mitigate photoinhibition on nitrifying bacteria even under strong light irradiation.